2018
DOI: 10.1016/j.heliyon.2018.e00764
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of degraded landscapes for ecosystem services in North-Western Ethiopia

Abstract: Establishing exclosures has become common in Ethiopia, especially in the central and northern highlands, where they serve as a response to persistent forest degradation, affecting forest resources and ecosystem services. We investigated changes in vegetation composition, aboveground biomass and soil properties after establishing an exclosure on degraded communal grazing land in Aba-Gerima watershed, North-Western Ethiopia. We selected 4-yr-old exclosure and paired the selected exclosure with an adjacent commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 49 publications
(72 reference statements)
9
40
1
3
Order By: Relevance
“…Less soil disturbance, greater vegetation cover, and organic input from grazing animals would improve the SOC in the upper position. Similarly, Mekuria et al [25] reported better vegetation cover and biomass in communal grazing lands in the upper position than in the lower position, which is more easily accessed by livestock that induce changes in SOC. Zhu et al [30] also found an increasing trend in SOC content for cropland and a decreasing trend in grassland from the summit to the lower part of a watershed in China.…”
Section: Effects Of Land-use Type On Soc and Tn Contents And Stocks Amentioning
confidence: 89%
“…Less soil disturbance, greater vegetation cover, and organic input from grazing animals would improve the SOC in the upper position. Similarly, Mekuria et al [25] reported better vegetation cover and biomass in communal grazing lands in the upper position than in the lower position, which is more easily accessed by livestock that induce changes in SOC. Zhu et al [30] also found an increasing trend in SOC content for cropland and a decreasing trend in grassland from the summit to the lower part of a watershed in China.…”
Section: Effects Of Land-use Type On Soc and Tn Contents And Stocks Amentioning
confidence: 89%
“…We followed the judgment sampling method (USEPA (United State Environmental Protection Agency) 2002) to locate representative sampling sites for both treated and control sub-watersheds, landscape positions (upper (3031-3156 masl) and lower (2947-3024 masl)), and land-use types (crop and grazing) at two soil depths (0-15 cm and 15-30 cm) (Wolka et al 2011;Mekuria et al 2018). Consequently, a total of 48 samples were collected (2 sub-watersheds × 2 landscape positions × 2 land uses × 2 depths × 3 replications).…”
Section: Soil Samples Collectionmentioning
confidence: 99%
“…The result of this study is in line with the findings of Abebe et al (2014) in Siltie area from South Ethiopia who reported significantly greater CEC in eight years old (young) exclosures. Higher CEC was also reported in a four-year old exclosure than adjacent grazing land in Gojam, Northwestern Ethiopia (Mekuria et al, 2018). Exchangeable Ca, Mg, and K varied significantly (P<0.05) between exclosures and the grazing land (Table 6).…”
Section: Soil Chemical Properties Soil Ph Electrical Conductivity (Ementioning
confidence: 81%
“…The disturbance of natural ecosystems in Ethiopia causes widespread soil degradation (soil erosion, nutrient depletion, and salinization) (Girmay et al, 2008), and ecosystem services (Mekuria et al, 2018). Particularly, soil loss, nutrient depletion, and a decline in soil quality are some of the manifestations of land degradation (Haile et al, 2006).…”
Section: Introductionmentioning
confidence: 99%